COMPARATIVE SEMANTICS OF GENDER IN PHRASEOLOGICAL UNITS: ENGLISH VS. UZBEK - Mukhammadieva Maftuna Khamidullaevna (World Scientific Research Journal, 2025)
This article explores the comparative semantics of gender in English and Uzbek phraseological units. Gender is not only a grammatical or social category but also a conceptual field deeply rooted in cultural traditions, values, and collective memory. Phraseology, as a system of stable language units with figurative meanings, plays a central role in the representation of gender stereotypes, roles, and evaluative judgments. The paper analyzes the semantic content of gendered idioms and proverbs in both English and Uzbek, focusing on metaphorical models, evaluative connotations, and the cultural worldview reflected in phraseology. A comparative approach highlights both universal and culture-specific patterns in the conceptualization of masculinity and femininity. The findings reveal that while English and Uzbek phraseology share common semantic features such as the association of men with strength and authority, and women with beauty and morality, there are also significant differences determined by historical, religious, and socio-cultural factors. The study concludes that phraseological gender semantics is a mirror of cultural identity, and its comparative study contributes to the broader understanding of linguistic worldview and intercultural communication.